Modelling considerations in probabilistic performance-based seismic evaluation case study of the I-880 viaduct. - Kunnath, Sashi K.
Limitations associated with deterministic methods to quantify demands and develop rational acceptance criteria have led to the emergence of probabilistic procedures in performance-based seismic engineering. The Pacific Earthquake Engineering Research performance-based methodology is one such approach. In this paper, the impact of certain modelling decisions made at different stages of the evaluation process on the performance assessment of a typical multi-bent viaduct is examined. Modelling, in the context of this paper, covers hazard modelling, structural modelling and loss modelling. The specific application considered in this study is a section of an existing viaduct in California: the I-880 interstate highway. Several simulation models of the viaduct are developed, a series of nonlinear time-history analyses are carried out to predict demands, measures of damage are evaluated and the probability of closure of the viaduct is estimated using the specified hazard for the site. It is concluded that the methodology offers several advantages over existing deterministic performance-based procedures. Results of the investigation indicate that the assessment methodology is particularly sensitive to the reliability of decisions made by bridge inspectors following a seismic event, and to the dispersion in the demand estimation, which in turn is influenced by several factors including soil?structure interaction effects and ground motion scaling procedures.
Keywords: Bridge; Fragility functions; Nonlinear time-history analysis; Performance-based seismic engineering; Seismic evaluation; Soil?foundation interaction